Attitude towards People with Disability of Nursing and Physiotherapy Students - Petronila Oliva Ruiz; Gloria Gonzalez-Medina; Alejandro Salazar Couso; María Jiménez Palomares; Juan Rodríguez Mansilla; Elisa María Garrido Ardila; María Nieves Merchan Vicente (MDPI AG, 2020)
Background: Attitudes are a component of our behaviour. Health professionals should have a global perspective of disability. They must provide treatment to people with disability and care for them, but they also should accept them with no judgements or discrimination. The general objective of this study was to know the attitude towards people with disability of nursing and physiotherapy students at the University of Cadiz. Methods: This was a descriptive, correlational, transversal and synchronous study. A total of 200 students participated in the study (91 from the bachelor's degree in nursing and 109 from the bachelor's degree in physiotherapy). The 'Attitudes towards people with disability scale' was used. Results: The mean score for both groups of students was 157.05 (SD = 14.14). Conclusions: Attitudes towards disability of nursing and physiotherapy students at the University of Cadiz tend to be positive. However, this was considered not sufficient since they will be health professionals in the future.